Action Research : Desain Penelitian Integratif Untuk Mengatasi Permasalahan Masyarakat - - Hasan (AKSES: Jurnal Ekonomi dan Bisnis, 2009)
This paper offers an action research approach as the method of research that should be done in universities while enhancing the integration of educational activities, research, and community service. This paper discusses some important aspects of action research such as understanding, processes, principles, applications and types of action research. After that, also put forward the implementation agenda and examples of action research that needs to be done and can be emulated by the academic community colleges in order to solve real problems in society.Keywords: action research, research methodology, community service